Unit Commitment with Tunable Frequency Response from Wind Turbine Generators. Issue 1 (January 2021) - Liu, Juelin; Yu, Juan; Rui, Song; Huang, Junkai; Xuebin, Wang; Li, Wenyuan
Abstract: Based on the natural inertia on the rotors, wind turbine generators can provide both inertia response and primary frequency response to support the system frequency stability. In this paper, by considering the coordinated optimization of frequency response, a unit commitment with tunable frequency response from wind turbine generators is proposed. The relationship between inertia response and primary frequency response is analyzed. A frequency response correlation constraint is proposed to eliminate the second frequency nadir. Considering the system frequency stability constraints and the feasible region of frequency response provided by wind turbine generators, a security-constrained unit commitment model with tunable frequency response is established. According to the actual operation mode of the power system, a bi-level algorithm is adopted to calculate the frequency response parameters of wind turbine generators. The simulation result of the GB 2030 system demonstrates that the proposed method can reduce operating costs while ensuring system stability.